Effects of Lactobacillus plantarum and fibrolytic enzyme on the fermentation quality and in vitro digestibility of total mixed rations silage including rape straw - Qin-hua LIU; Xiang-yu LI; Seare T Desta; Jian-guo ZHANG; Tao SHAO (Journal of Integrative Agriculture, 2016)
Abstract: The aim of the current study was to investigate the effects of a lactic acid bacteria inoculant (Lactobacillus plantarum, LP), fibrolytic enzyme (EN), combination of LP and EN (LP+EN) on fermentation quality, nutritive characteristics and in vitro digestibility of total mixed ration (TMR) silages containing 0, 7.5 and 15.0% (on dry matter basis) of rape (Brassica campestris L.) straw (RS) (denoted as CTMR, LTMR and MTMR, respectively). After ensiling for 60 days, TMR silages without additives were well preserved, but MTMR had higher pH than CTMR and LTMR. There were no differences in other parameters of fermentation quality, microbial composition, nutrition and in vitro digestibility between CTMR and LTMR except for yeast and mold number and crude protein (CP) content. CTMR and LTMR silage had higher CP content, in vitro neutral detergent fiber digestibility (IVNDFD) and in vitro acid detergent fiber digestibility (IVADFD), lower acid detergent fiber (ADF) content than MTMR silage. LP and EN decreased pH and increased dry matter (DM) recovery of TMR silages. LP+EN improved the fermentation quality, nutritive characteristics and in vitro digestibility of TMR silages, showed by lower pH, ADF content, higher lactic acid content, in vitro dry matter digestibility (IVDMD) and IVNDFD. Therefore, It was suggested that TMR silage contained 7.5% RS on a DM basis and treated with LP+EN can be as a useful feed for ruminant.